Contest of best practices tackling social inequalities in cancer prevention: an iPAAC initiative. (20th October 2021) - Hernandez-Garcia, M; Salas-Trejo, D; Anttila, A; Lipponen, S; Vanaclocha-Espí, M; Pinto-Carbó, M; Molina-Barceló, A
Abstract: Issue: Many cancer risk and protection factors have socially determined conditions. In general, those who pertain to lower socioeconomic groups are more exposed to cancer risk factors and less to protective ones. Description of the problem: Current programmes on health promotion and early detection of cancer yield different results according to social group, perpetuating health inequalities. Contest of best practices tackling social inequalities in cancer prevention is an initiative emerged in the framework of Innovative Partnership for Action Against Cancer (iPAAC). This contest identifies interventions proven effective to reduce social inequalities in cancer prevention, with the aim of sharing lessons learned and facilitating replication. Best practice is defined as an intervention implemented in a real life setting which has been favourably assessed in terms of adequacy, effectiveness, and equity. Assessment was conducted on a peer-review basis. To be accepted for evaluation, practices ought to meet compulsory criteria: relevance, equity, and effectiveness; they were further assessed according to gender perspective, efficiency, ethics, sustainability, inter-sectors collaboration, transferability, innovation, evidence based, and public engagement. Results: Overall, 15 proposals were submitted from: Belgium, France, United Kingdom, Italy, Slovenia, and Spain. Six out of fifteen (40%) fell under the scope of health promotion; eight proposals (53%) addressed cancer screening. One single practice (7%) approached both primary and secondary prevention. Eleven proposals (73%) were considered best practices. Full details are available at www.ipaac.eu/en/contest-best-practices . Lessons: These results suggest that a combination of public health universal interventions together with targeted interventions is effective in preventing cancer in the whole population, integrating specific actions for specific groups otherwise not reached by universal prevention activities. Key messages: This contest contributes to provide insight on effective strategies that can be translated to other settings and adapted into more equitable new procedures. Tackling inequities should be included in future best practices criteria.